INNOVATIVE APPROACHES TO CONSCIOUS FAMILY FORMATION THROUGH THE INTEGRATION OF PSYCHOLOGICAL MODELS AND ENERGY PRACTICES - Полєхіна, Анна (SWorldJournal, 2026)
The article is devoted to innovative approaches to the conscious formation of a family through the integration of psychological models and energy practices. The purpose of the study is to analyze modern approaches to the formation of a family as a holisti